Insights into the mechanism of formation of non-conventional cochleates and its impact on their functional properties - Shuddhodana (2022)
The consequences of design of drug delivery system such as lipid cochleates are crucial on the functional outcome. This study describes the design, mechanism of formation and functional properties of Amikacin-bridged cochleates with and without the presence of sub-threshold concentration of Ca2+ in comparison to conventional Ca2+-bridged cochleates. The DOPS cochleates were successfully prepared with Ca2+, Amikacin, and Amikacin + sub-threshold Ca2+ as bridging agents. Synergistic bridging of the DOPS headgroups occurred in the presence of Amikacin + sub-threshold Ca2+ resulting in rigidly packed multiple bilayers with uniform lamellar repeat distance of 51 Å. The rigidity of the internal structure of the cochleates increased with increasing concentration of Ca2+. As a consequence, an increase in Amikacin encapsulation (71.63 ± 8.98%) and loading (266.70 ± 12.01 mg Amikacin/g cochleates) was obtained. Additionally, the in-vitro Amikacin release rate decreased as the concentration of Ca2+ was increased reflecting the tightly packed structures and suggesting sustained release. Drug release kinetics studied using the Higuchi model suggested tuneable Amikacin release by simply varying the Ca2+ concentrations used for cochleation. The use of higher Ca2+ concentration positively affected the long-term stability of the cochleates and showed increased half-lives during 12 weeks of storage. The proposed mechanistic model of the formation of non-conventional cochleates is supported well by the analytical data and promotes the synergistic effect of the bridging agents. This study reveals the importance of the type and concentration of the bridging agent to achieve a specific functional outcome and has the benefit to guide future design of cochleates with specific functions in drug delivery and formulation.